PENYULUHAN ALUR PELAYANAN RADIOLOGI DI PUSKESMAS REJOSARI KOTA PEKANBARU - Aulia Annisa; R. Sri Ayu Indrapuri; Asshy Artata; Aylsa Salsabilla; Darmawan Fitriansyah (LPPM Universitas Awal Bros, 2026)
Radiolog also known as x-rays, is a crucial supporting medical procedure in the diagnostic process, producing images of internal organs. Radiology examinations utilize X-rays to detect abnormalities and help doctors determine the appropriate medical treatment. In Indonesia, radiology services can only be provided in hospital-level health facilities because they require standardized equipment and medical personnel. Meanwhile, community health centers (Puskesmas), as primary health care facilities, play a role in providing promotive and preventive services and referring patients to advanced health care facilities, including for radiology examinations. Puskesmas patients who utilize referral services often encounter difficulties understanding the radiology service process, particularly regarding differences in administrative procedures based on the type of financing, such as BPJS Kesehatan (Healthcare Social Security), private insurance, and general insurance. This often leads to confusion and delays in service delivery. To address these challenges, direct counseling for Puskesmas patients is a strategic step. Through face-to-face counseling, both individually and in groups, patients can receive detailed information about procedures, required documents, and service stages according to their chosen financing type.This counseling aims to improve public understanding of the radiology service process, reduce administrative errors, and expedite the service process. Through interactive, direct delivery, patients can obtain solutions to specific challenges they face. It is hoped that this education will create more efficient, transparent radiology services and facilitate patient access to the healthcare they need.